Dombra: Types, Distribution Area, and Its Role in Epic Art - Sharip, А.Ж. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2024)
The dombra is a musical instrument that plays a significant role in the cultures of Turkic peoples (Kazakhs, Uzbeks, Bashkirs, Nogais, Tatars, Lakais) and several other ethnic groups (Tajiks, Kalmyks, Hazaras). This article examines not the use of the dombra in instrumental music, but its role in the art of epic singing. This topic has not been specifically studied from a scholarly perspective before. The author utilizes photo, audio, and written materials collected during foreign research trips to scientific centers, museums, and informants. Some information about the dombra was recorded on video by Uzbek bakhshis. The specifics of dombra craftsmanship are discussed based on the experience of masters. The connection between the dombra and shamanic practices, as well as the tradition of its veneration among epic singers, is explored. The article presents hypotheses about the origin of the name "dombra" and corresponding opinions. The article uses comparative-historical, synchronic, and structural-functional research methods. The research results demonstrate that the traditional oral poetry of Turkic peoples was created in conjunction with music, and that epic singers and improvising poets performed their works accompanied by musical instruments, including the dombra. The geographical area of the instrument's distribution is found to be quite extensive.